Polystyrene microplastics exposition on human placental explants induces time-dependent cytotoxicity, oxidative stress and metabolic alterations - de Sousa, Ashelley Kettyllem Alves; Pires, Keyla Silva Nobre; Cavalcante, Isadora Hart; Cavalcante, Iasmin Cristina Lira; Santos, Julia Domingues; Queiroz, Maiara Ingrid Cavalcante; Leite, Ana Catarina Rezende; Crispim, Alessandre Carmo; da Rocha Junior, Edmilson Rodrigues; Aquino, Thiago Mendonça; Weingrill, Rodrigo Barbano; Urschitz, Johann; et al. (Frontiers in Endocrinology, 2024)
Microplastics (MP) are environmental pollutants with the potential to harm living organisms. MPs have been shown to accumulate in human organs, including the placenta. Here, we investigated the biochemical impact of 5 μm polystyrene microplastics (PS-MP) on term placental chorionic villi explants, focusing on cytotoxicity, oxidative stress, metabolic changes, and the potential of MP to cross the placental barrier. Placental explants were exposed to 100 μg/mL of PS-MP for 72 hours. A significant increase in cytotoxicity over time (p < 0.01) could be observed by lactate dehydrogenase (LDH) release assay. Mitochondrial and overall superoxide anion (p < 0.01 and p < 0.05, respectively) and hydrogen peroxide (p < 0.001) were substantially increased. PS-MP exposure led to a reduction in total sulfhydryl (SH) content (p < 0.05) and the activities of antioxidant enzymes superoxide dismutase (SOD, p < 0.01) and catalase (CAT, p < 0.05), whereas glutathione peroxidase (GPx) activity increased (p < 0.05) and the oxidized/reduced glutathione ratio was diminished (p < 0.05). Markers of oxidative damage, such as malondialdehyde and carbonylated proteins, also increased significantly (p < 0.001 and p < 0.01, respectively), indicating altogether oxidative stress. A metabolomics analysis revealed significant differences between control and PS-MP exposed groups, with reduced levels of alanine, formate, glutaric acid, and maltotriose. In conclusion, the study demonstrates that a high concentration of PS-MP induces time-dependent cytotoxicity, oxidative stress, and changes in the TCA cycle, and in the folate, amino acid and energetic metabolisms. As such, it is paramount to expand our research efforts to elucidate the comprehensive effects of MP contamination on pregnancy, and the repercussions on the subsequent generations.